(untitled) (Cadernos de Sociomuseologia, 2025)
In this thesis, we will address a topic that, despite being pointed out as central by the main actors in the field of Sociomuseology, has not yet received an in-depth study: identifying and systematizing the role of educator Paulo Freire in museums and Museology, establishing direct theoretical influences and recognizing socio-educational guidelines for the construction of a museological theory and practice focused on the conscious exercise of citizenship. Freirean pedagogy has largely been a mainstay for Sociomuseology, the writings about it have been punctuating the relationship or even the influence of Paulo Freire in the formulation of his concepts and paradigms, just a closer look is enough to perceive the presence of Freirean thought in Sociomuseology, either in discourse or in its praxis. Not only in extension will Paulo Freire’s work be integrated, but there is still room for deepening and intensifying its use in the field of museums and Museology(s). Possibilities that assert and confirm each day, with the emphasis on the educational function of museums, where this is less and less an exclusive activity of a specific section, but is potentially integrated into all museum activities, no longer just an instrument auxiliary of formal education, but a space of permanent education, throughout life, focused on citizenship and respect for cultural diversity, a museological theory and practice committed to the community, with the conscious exercise of citizenship and Freirean style. A radical, critical and dialogical pedagogy adds a new perspective to Sociomuseology in its theoretical-applied field, leading it to hope in a learning process committed to life. Keywords: Sociomuseology – Paulo Freire – Education – Citizenship – Hope